Host Resistance, Bioagents, Botanicals, Nutrients and Fungitoxicants Approaches for Management of Spot Blotch in Wheat Incited by Bipolaris sorokiniana - Prasad, Durga; Kumari, Manisha; Manohariya, Gajendra; Panwar, Chakshu; Pahima, D. V. (International Journal of Bio-resource and Stress Management, 2026)
Wheat (Triticum aestivum L.) is one of the most widely cultivated crops and a staple food for millions worldwide. In India, it ranks as the second most important cereal after rice. However, wheat productivity is significantly impacted by abiotic and biotic stresses, with diseases posing a major challenge. Various pathogens, including nematodes, viruses, bacteria, necrotrophic fungi, and biotrophic fungi, attack wheat, resulting in substantial yield and quality losses. Among fungal diseases, spot blotch, caused by Bipolaris sorokiniana, is a major threat to wheat cultivation, particularly in the North Eastern Plain region of India. Most often, the pathogen causes symptoms on the leaf and sheath. Additionally, the spikes may be impacted, resulting in low-weight, shriveled grains with a dark tip at the kernel embryo end. Spot blotch symptoms initiated as small, light brown lesions scattered throughout the leaves. As the disease worsens, these lesions enlarge into huge, oval to oblong spots. This disease, prevalent in warm and humid climates, can reduce wheat yields by 15% to 20% and adversely affect grain quality. Even a slight reduction in spot blotch severity through effective disease management strategies can significantly improve farmers’ income. This review comprehensively analyzes the impact of micronutrients, botanicals, bioagents, and fungitoxicants on Bipolaris sorokiniana under both in vivo and in vitro conditions. Additionally, it presents detailed insights into host resistance mechanisms against spot blotch, offering valuable information for researchers, agricultural professionals, and farmers.